Relationship Between Milk Feeding Habits and Nursing Bottle Syndrome Among Selected Preschool Children in Serdang, Selangor Darul Ehsan - Syahrial, Dasrilsyah (1993)
The objectives of the study were: (1) to identify the prevalence of nursing bottle syndrome among preschool children; (2) to investigate the relationship between nursing bottle syndrome and dietary factors such as frequency of milk intake, number of sugar-related food consumed, the duration of bottle feeding and the amount of sugar added to bottle feeding; (3) to determine the relationship between parents' demographic and socio-economic characteristics such as education, income and number of children in the family and the prevalence of nursing bottle syndrome; (4) to determine the relationship between nursing bottle syndrome and parents' attitudes towards proper feeding and dental care. Seven preschools consisted of five kindergartens, one nursery and one preschool laboratory were purposively selected for the study. Data were gathered through clinical screening of children and by interviewing the parents using a set of questionnaire. A total of 153 out of 284 children examined were found to have nursing bottle syndrome. About 52.0% of the subjects were females and the others were males. The average age was 5.1 years. About 81.0% of the respondents were mothers and 19.0% were fathers. The average age of the respondents was 36.0 years. The relationship between nursing bottle syndrome and the independent variables of the study were tested u sing the Pearson product-moment correlation. Simple multiple regression analysis was also done to determine the predictor variables of nursing bottle syndrome and the total contribution of the independent variables to the dependent variable. The findings revealed that the prevalence of nursing bottle syndrome was high (53.8%). The test of relationship indicated that the prevalence of nursing bottle syndrome was positively related to duration of bottle feeding (r=0.2263; P=0.00.), household income (r=0.3163; P=0.00.), number of children in the family (r=0.1287 ; P=0.015) and number of sugar-related food consumed (r=0.1280; P =0.016) but was negatively related to frequency of milk intake (r=-0.1415; P=0.008), and parents' attitudes (r=-0.1385; P=0.010). The results of multiple regression analysis indicated that five variables namely, level of parents' education, duration of bottle feeding, household income, parents' attitudes and frequency of taking milk were good predictors of nursing bottle syndrome and explained 23.3% of the variance in the incidence of nursing bottle syndrome. To minimise the prevalence of nursing bottle syndrome, it is recommended that parents should be made aware of the problems of the disease. They also need to be educated on proper feeding habits and oral hygiene of their children. One way to achieve this is by conducting massive campaigns to disseminate child feeding and dental health information and to educate parents on the preventive methods of nursing bottle syndrome. The use of films, slides, posters, etc., can be effective in achieving this objective.